The hemostatic profile of cold-stored whole blood from non-greyhound and greyhound dogs over 42 days - Cooper, James L.; Sharp, Claire R.; Boyd, Corrin J.; Claus, Melissa A.; Rossi, Gabriel (Frontiers in Veterinary Science, 2023)
Objectives To compare the hemostatic characteristics of cold-stored whole blood (CSWB) from non-greyhound dogs (NGD) and greyhound dogs (GD) over 42 days of storage, notably, platelet closure time (PCT) (NGD only), manual platelet count (PLT) (GD only), ellagic acid (INTEM) and tissue factor activated (EXTEM) rotational thromboelastometry, prothrombin (PT) and activated partial thromboplastin time (aPTT), fibrinogen concentration (FIB), and the activities of factors (F) FII, FV, FVII, FVIII, FIX, FX, FXIII antigen (FXIII:Ag), and von Willebrand factor antigen (vWF:Ag). Design Whole blood from 10 NGD and 10 GD, was refrigerated in CPD blood bags at 4°C for 42 days. Blood was analyzed before refrigeration (day 0) and at day 1 (d1), 3, 5, 7, 10, 14, 17, 21, 24, 28, 31, 35, 38, and 42. Multivariate linear mixed effects models were created to evaluate coagulation parameters over time and compare NGD and GD. Data are summarized as estimated marginal means with 95% confidence intervals. Significance was set at P < 0.05. Results The PCT for all NGD CSWB was above the device limit by d7. The PLT for GD CSWB did not change during storage. The mean alpha-angle for INTEM and EXTEM decreased to <50% of baseline at d38 and d31 for NGD, and d31 and d17 for GD CSWB. The mean maximum clot firmness (MCF) for INTEM and EXTEM reduced to <50% of baseline at d42 and d28 for both GD and NGD. PT and aPTT for NGD and GD increased over time. For NGD CSWB, the mean FVIII and vWF:Ag activities decreased to <50% of baseline at d7 and d28, respectively, and FIB reached 0.982 g/dL by d24. For GD CSWB, FVIII, FXIII:Ag and FV activities decreased to <50% of baseline by d3, d38, and d38, respectively, and FIB was 0.982 g/dL at baseline. Alpha-angle and MCF for both INTEM and EXTEM, and activities for FII, FV, FIX, FXIII:Ag were significantly lower, and vWF:Ag was significantly higher overall in GD CSWB compared with NGD. A significant difference in the pattern of change over time was detected between NGD and GD in EXTEM alpha-angle, INTEM and EXTEM MCF, FII, and FVIII activities. Conclusions The in vitro viscoelastic parameters of GD and NGD CSWB declines over 42 days, but numerous hemostatic parameters (INTEM and EXTEM alpha-angle and MCF, activity of FII, FV, FV, FVII, FIX, FX, FXIII:Ag, vWF:Ag, and FIB) remain within 50% of baseline for more than 14 days. CSWB from GD compared to NGD has reduced hemostatic activity overall, but a similar pattern of decline for most parameters over time.